Are Cities Safer Than Before? - Huang, Guangwei (Frontiers in Sustainable Cities, 2021)
Cities are built to lead better lives. However, irrational urban development has led in reverse, causing numerous problems. The increase in flood risk in urbanized areas is one of the significant problems. Despite extensive research, numerous engineering projects have been carried out to reduce the risk of flooding, the question “are we safer than before?” remains underexplored. The present work is a case study aimed at providing new evidence of the current state of flood disaster management. It analyzed the relationship between the magnitude of flood and resultant flood fatality and property damage in the target area over a long period of time and found that we are safer now than before in terms of life loss, but not safer than before in terms of flooding impacts on livelihood. Most importantly, it was found that flood risk management in the region continues to be critically dependent on structural measures. Besides, it highlighted a contrast between having a well-developed emergency information delivery system and its ineffectiveness in mobilizing evacuation.